Students’ Perception of the Use of American and British Accents in Movies and Songs - Utami, Imelda Putri; Norahmi, Maida; Farid, Rezqan Noor; Hayati, Sifa (Journal of English Language and Education, 2026)
This study examines how students perceive American and British accents, particularly when these accents are presented through films and songs used in English learning. Since such media are frequently incorporated into classroom activities, the type of accent used can influence how well students comprehend and engage with the material. The purpose of the research is to identify which accent students find easier to understand and more helpful for developing their English skills through audiovisual input. The study involved 35 sixth-semester English Education students from Class C at Universitas Palangka Raya. Data were collected using a mixed-method questionnaire adapted from Hermini (2019), with several additional questions developed by the researcher. Results show a clear preference for the General American (GA) accent, which students described as easier to follow due to its clarity, widespread use, and familiarity. On the other hand, although Received Pronunciation (RP) was seen as distinct, formal, and culturally prestigious, many found it more difficult to grasp. Interestingly, 100% participants said GA was easier to understand in songs, and 94.3% said the same for movies. The findings suggest that consistent exposure to a particular accent improves listening comprehension. Therefore, educators should consider prioritizing materials that feature GA, while gradually introducing RP to help learners build broader listening skills over time.